2012
DOI: 10.3389/fneng.2012.00001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a clinical olfactory test with an artificial nose

Abstract: Clinical olfactory tests are used to address hyposmia/anosmia levels in patients with different types of olfactory impairments. Typically, a given test is employed clinically and then replaced by a new one after a certain period of use which can range from days to several months. There is a need to assess control quality of these tests and also for a procedure to quantify their degradation over time. In this paper we propose a protocol to employ low-cost artificial noses for the quantitative characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Overall, these factors can make human ECoG experiments less controlled than non-invasive neuroscientific studies in healthy human subjects or invasive studies in animals. At the same time, in these respects, our present study is similar to the many other ECoG-based studies that have been described in the literature [37, 17, 23, 16, 22, 18, 39]. Despite the issues described above, the results presented in our present and other ECoG studies are usually consistent with expectations based on the general human neuroanatomy or on results from other imaging modalities.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Overall, these factors can make human ECoG experiments less controlled than non-invasive neuroscientific studies in healthy human subjects or invasive studies in animals. At the same time, in these respects, our present study is similar to the many other ECoG-based studies that have been described in the literature [37, 17, 23, 16, 22, 18, 39]. Despite the issues described above, the results presented in our present and other ECoG studies are usually consistent with expectations based on the general human neuroanatomy or on results from other imaging modalities.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies [47, 22, 37, 12, 23, 16, 38, 35] have demonstrated retrospectively that individual brain processes, such as movement, movement planning or auditory processing can be reliably decoded from ECoG signals. However, it was not clear to what extent these decoding models could be applied in real time or generalize over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These potentials originate approximately two seconds prior to movement onset developing the Bereitschafts potential (BP) or readiness potential (RP) [35], and rebound during movement execution developing the motor potential (MP). BPs have been used to detect movement intention [36], [37] while MPs have been used to detect movement parameters such as direction [31], [38]. In these approaches the extracted motor information are general movement parameters (i.e., the intention to move, the direction of the movements) usually detected before movement onset or just after movement initiation.…”
Section: Discussionmentioning
confidence: 99%